Analisis Perbandingan Pengalaman Pengguna pada Aplikasi Virtual Hotel Operator di Kota Malang menggunakan User Experience Questionnaire (UEQ) dan Importance Performance Analysis (IPA) (Studi RedDoorz dan OYO) - Azrul Ananda; Bondan Sapta Prakoso; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
In the present era, technology can be used as a means of anything such as a means for the hospitality industry. The sharing economy business model is a technology that is suitable for the world of hospitality or lodging, such as the Virtual Hotel Operator (VHO). RedDoorz and OYO are the two most dominant VHO applications and are competing with each other in Indonesia. The researchers conducted a review on the Play Store or the App Store, the researcher found some problems posed by the users to ascertain both applications. The researchers wanted to do a comparison on both VHO such. Analysis was performed using the User Experience Questionnaire (UEQ) which will find out the user experience after using the application and will determine which one is more convenient to use by the user of the second VHO such. To interpret the results of the UEQ attribute, an analysis was carried out using the Importance Performance Analysis (IPA) method which is useful for measuring customer satisfaction and presenting it graphically so that recommendations for action can be made. Data analyzed with Microsoft Excel. The results of the user experience analysis obtained from 30 respondents using UEQ user experience on the application of OYO more superior than RedDoorz of all aspects of the assessment. The results of the analysis of the IPA there are 1 scale on the quadrant I and II for each application, in quadrant III there is 1 scale on RedDoorz and 2 scales on OYO, in quadrant IV there are 3 scales on the app RedDoorz and 2 scales on the app OYO.